Beam emittance measurement for the PLS-II linac - Byung Joon Lee (2018)
© 2016, The Korean Physical Society. The second-generation Pohang Light Source (PLS-II) has a 100-MeV pre-injector for the 3-GeV linac. A thermionic gun produces an electron charge of 200 pC with a bunch duration of 500 ps by using a 250-ps triggering pulser. At the pre-injector, one of the most important beam parameters for identifying the beam quality is the transverse emittance of electron bunches. Therefore, we measure the beam emittance and the Twiss functions at 100 MeV in order to match the beam optics to the beam transport line and go through it to the storage ring. To measure the transverse emittance, we used a well-known technique, the quadrupole scan, at the pre-injector. The emittances were 0.591 mm-mrad in the horizontal direction and 0.774 mm-mrad in the vertical direction.